Pengaruh Penyuluhan Ibu Hamil Terhadap Pemberian ASI Ekslusif - Melia Puspita Sari; Febi Ratnasari (Malahayati Nursing Journal, 2021)
ABSTRACT: THE EFFECT OF COUNSELING PREGNANT WOMEN ON EXCLUSIVE BREASFEEDING Background: Coverage of breastfeeding in Indonesia in 2015 was only 55.7% and when referring to the 2015 strategic plan target of 39%, nationally the scope of exclusive breastfeeding for infants aged less than 0 to 6 months has met the target. The percentage of exclusive breastfeeding in infants aged 0-6 months in Banten Province in 2016 was 61.6%, a slight increase compared to the percentage of exclusive breastfeeding in 2015 which was only 60.7%. The regency / city with the lowest percentage of exclusive breastfeeding was Pandeglang, which was 19.88%, followed by Serang City at 39.77% (Indonesian Health Profile, 2018). As a result of not providing exclusive breast milk will have an impact on infant health including the incidence of diarrhea, infection and malnutrition. Method: the analytical method used is the method of analysis of journal contents. Readable journals must be read and examined to be clear in analyzing these journals. And an analysis is made of the contents obtained from the research objectives and the results of the research. Searching this literature review through an accredited journal site namely google schoolar, PubMed and using literature from 2016-2020. Results: 67 journals were obtained using keywords and filtered again based on inclusion criteria and obtained literature results that met the requirements of 20 journals. Conclusion: Thus it can be concluded that there is an effect of counseling on pregnant women regarding the administration of colostrum breast milk. Keywords: influence of counseling, exclusive breastfeeding and exclusive breastfeeding  INTISARI: PENGARUH PENYULUHAN IBU HAMIL TERHADAP PEMBERIAN ASI EKSLUSIF Latar Belakang: Cakupan pemberian ASI di Indonesia pada tahun 2015 hanya sebesar 55,7% dan jika mengacu pada target renstra di tahun 2015 yang sebesar 39% maka secara nasional cakupan pemberian ASI ekslusif pada bayi usia kurang dari 0 sampai 6 bulan telah memenuhi target. Presentase pemberian ASI Ekslusif pada usia bayi 0-6 bulan di Provinsi Banten pada tahun 2016 sebesar 61,6%, sedikit meningkat jika dibandingkan dengan presentase pemberian ASI ekslusif pada tahun 2015 yaitu hanya sebesar 60,7%. Kabupaten/Kota dengan presentase pemberian ASI ekslusif terendah adalah Kabupaten Pandeglang yaitu 19,88%, diikuti dengan Kota Serang sebesar 39,77%. Akibat dari tidak diberikannya asi ekslusif akan berdampak kepada kesehatan bayi antara lain angka kejadian diare, infeksi dan kekurangan gizi.Metode: metode analisis yang digunakan ialah metode analisis isi jurnal. Jurnal yang dapat dibaca harus dibaca dan dicermati supaya jelas dalam menganalisis jurnal-jurnal tersebut. Dan dibuat analisa mengenai isi yang didapat dari tujuan penelitian dan hasil penelitian tersebut. Penelusuran literatur riview ini melalui situs jurnal yang sudah terakreditasi yaitu google schoolar, PubMed dan menggunakan literatur dari tahun 2016-2020.Hasil: didaptkan 67 jurnal menggunakan kata kunci dan dan disaring lagi berdasarkan kriteria inklusi  dan didapatkan hasil literatur yang memenuhi syarat sebanyak 20 jurnal.Kesimpulan: demikian dapat disimpulkan bahwa ada pengaruh penyuluhan terhadap ibu hamil tentang pemberian asi kolostrum. Kata kunci: pengaruh penyuluhan,asi ekslusif dan exclusive breastfeeding.